Sensitive chiral high-performance liquid chromatographic determination of anthelmintic flubendazole and its phase I metabolites in blood plasma using UV photodiode-array and fluorescence detection Application to pharmacokinetic studies in sheep - Nobilis, Milan; Vybíralová, Zuzana; Krízová, Veronika; Kubícek, Vladimír; Soukupová, Marie; Lamka, Jirí; Szotáková, Barbora; Skálová, Lenka (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2008)
Although benzimidazole anthelmintic flubendazole, methyl ester of [5-(4-fluorobenzoyl)-1H-benzimidazol-2-yl]carbamic acid, is extensively used in veterinary and human medicine for the treatment of gastrointestinal parasitic helminth infections, reliable data about its pharmacokinetics in various species have not been reported. Our previous work [M. Nobilis, Th. Jira, M. Lísa, M. Holcapek, B. Szotáková, J. Lamka, L.Skálová, J. Chromatogr. A 1149 (2007) 112-120] had described the stereospecificity of carbonyl reduction during phase I metabolic experiments in vitro. For in vivo pharmacokinetic studies, further improvement and optimization of bioanalytical HPLC method in terms of sensitivity and selectivity was necessary. Hence, a modified chiral bioanalytical HPLC method involving both UV photodiode-array and fluorescence detection for the determination of flubendazole, both enantiomers of reduced flubendazole and hydrolyzed flubendazole in the extracts from plasma samples was tested and validated. Albendazole was used as an internal standard. Sample preparation process involved a pH-dependent extraction of the analytes from the blood plasma into tert-butylmethyl ether. Chromatographic separations were performed on a Chiralcel OD-R 250 mm x 4.6mm column with mobile phase methanol-1M NaClO(4) (75:25, v/v) at the flow rate 0.5 ml min(-1). In quantitation, selective UV absorption maxima of 290 nm (for reduced flubendazole), 295 nm (for albendazole), 310 nm (for flubendazole) and 330 nm (for hydrolyzed flubendazole) were used in the UV photodiode-array detection, and lambda(exc.)/lambda(emis.)=228 nm/310 nm (for reduced flubendazole) and lambda(exc.)/lambda(emis.)=236 nm/346 nm (for albendazole) were set on the fluorescence detector. The fluorescence detection was approximately 10-times more sensitive than the UV detection. Each HPLC run lasted 27 min. The validated chiral HPLC-PDA-FL method was employed in the pharmacokinetic studies of flubendazole in sheep. The stereospecificity of the enzymatic carbonyl reduction of flubendazole was also observed in vivo. (+)-Reduced flubendazole was found to be the principal metabolite in ovine blood plasma and only low concentrations of hydrolyzed flubendazole, the parent flubendazole and (-)-reduced flubendazole were detected in this biomatrix.
Keywords: ovce domácí; Male; fluorescenční spektrometrie; Stereoisomerism; vysokoúčinná kapalinová chromatografie; Sheep, Domestic; Mebendazole; mužské pohlaví; reprodukovatelnost výsledků; Reproducibility of Results; Chromatography, High Pressure Liquid; Anthelmintics; Spectrophotometry, Ultraviolet; stereoizomerie; Animals; anthelmintika; zvířata; Sensitivity and Specificity; senzitivita a specificita; Spectrometry, Fluorescence; mebendazol; spektrofotometrie ultrafialová